THE INFLUENCE OF RETURN ON ASSETS, LEVERAGE, CAPITAL INTENSITY, AND CORPORATE GOVERNANCE TOWARDS TAX AVOIDANCE - Yolanda Rian Wiratama; Budi Kurniawan (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
This research was aimed to know the influences of return on asset, leverage, capital intensity, and corporate governance on tax avoidance. The population in this study were all property, real estate, and building construction companies listed on the Indonesia Stock Exchange in 2017 – 2019. The data used in this study was secondary data. The number of research samples obtained was 31 companies with purposive sampling technique and the number of observations of research data obtained was 93. This study used the multiple linear regression method with a random effects approach model. The results of this study are (1) return on asset has a significant negative effect on tax avoidance, (2) leverage has a significant positive effect on tax avoidance, (3) capital intensity has no effect on tax avoidance, (4) corporate governance has a significant negative effect on tax avoidance.